2015
DOI: 10.1177/2158244015571638
|View full text |Cite
|
Sign up to set email alerts
|

Building a “Better Life”

Abstract: Adolescent pregnancy is often described as a major concern in public health and is associated with negative outcomes for educational and career attainment. Our objective was to compare the future aspirations of pregnant and parenting adolescents and identify social or structural barriers that they experience in their daily lives using journal entries from pregnant and parenting adolescents. The journals, which served as primary data sources, were completed by 52 multi-ethnic pregnant and parenting adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
5
0
1
Order By: Relevance
“…On a positive note, the participants in this study shared their dreams and aspirations for the future. They envisioned completing their education and focusing on their dream careers and some verbalised the hope of contributing meaningfully to society [58,81]. Previous studies have shown that adolescent mothers can be resilient and that they can persevere to achieve a brighter future for themselves and their children, and most consider that their future is interconnected with that of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a positive note, the participants in this study shared their dreams and aspirations for the future. They envisioned completing their education and focusing on their dream careers and some verbalised the hope of contributing meaningfully to society [58,81]. Previous studies have shown that adolescent mothers can be resilient and that they can persevere to achieve a brighter future for themselves and their children, and most consider that their future is interconnected with that of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that adolescent mothers can be resilient and that they can persevere to achieve a brighter future for themselves and their children, and most consider that their future is interconnected with that of their children. A study by O'Brien Cherry et al [81] in Indiana in the US found that all 52 of the participating adolescent mothers aspired to provide a worthy future for their children by completing school and following a career. Adolescent mothers who had persevered through high school attributed their success to hope, confidence, determination, self-assurance, encouragement, intrinsic and extrinsic motivation, respect, and support from their teachers, alternative classes, the community, life skills programmes, and their peers [81].…”
Section: Discussionmentioning
confidence: 99%
“…The study population included female adolescents (15)(16)(17)(18)(19) years in the KEEA Municipality. A sum of 7,667 females (10-19 years), including both pregnant and non-pregnant adolescents represented the study population (50).…”
Section: Population and Samplingmentioning
confidence: 99%
“…There are several detrimental health, psychosocial, and economic consequences connected with AP that are disturbing and should not be underestimated (18)(19)(20)(21). Research till date has proven that pregnant females younger than 17 years have a higher incidence of health complications related to mother and child compared to grown-up women, though these complications may be more severe among youngest adolescents (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation